2019
DOI: 10.1021/acs.jced.9b00819
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase Mimic Activity of Au–Ag/l-Cys-rGO Nanozyme toward Detection of Cr(VI) Ion in Water: Role of 3,3′,5,5′-Tetramethylbenzidine Adsorption

Abstract: This study demonstrated the adsorption behavior of 3,3′,5,5′-tetramethylbenzidine (TMB) on graphene oxide (GO) and L-cysteine functionalized reduced graphene oxide (L-Cys-rGO) sheets for the first time. To investigate the adsorption phenomenon of TMB on GO and L-Cys-rGO sheets, the effect of different pH values, adsorbent concentrations, and adsorption times were explored. The abundant hydroxyl groups contained on the GO surface has played an eminent role in TMB adsorption. The presence of the −SH functional g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…34 While 2900 and 1390 cm −1 may be assigned to the stretching vibration and deformation vibration peaks of C−H, 3400 cm −1 is the stretching vibration peak of O−H, 1044 cm −1 is the stretching vibration peak of C−S, and the peak at 1600 cm −1 is the deformation vibration peak of N−H. These functional groups come from cysteine, 35,36 and the facts demonstrated that cysteine may act as a capping agent to stabilize the MnO 2 QDs. These results suggested that the Cys-MnO 2 QDs have been successfully synthesized by the simple one-step ultrasonic method.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…34 While 2900 and 1390 cm −1 may be assigned to the stretching vibration and deformation vibration peaks of C−H, 3400 cm −1 is the stretching vibration peak of O−H, 1044 cm −1 is the stretching vibration peak of C−S, and the peak at 1600 cm −1 is the deformation vibration peak of N−H. These functional groups come from cysteine, 35,36 and the facts demonstrated that cysteine may act as a capping agent to stabilize the MnO 2 QDs. These results suggested that the Cys-MnO 2 QDs have been successfully synthesized by the simple one-step ultrasonic method.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The co-doping of N and S on rGO nanosheets provides abundant functional groups to facilitate the interactions with TMB, thereby improving the catalytic efficiency. 46 Meanwhile, the large SSA of NiCo 2 S 4 @N,S-rGO increased the active sites of its precursor NiCo 2 S 4 . (2) Under irradiation of visible light, the electrons of NiCo 2 S 4 are excited at the conduction band (CB), holes are generated at the valence band (VB), and the transfer from CB to VB is promoted by N and S-doped rGO.…”
Section: Resultsmentioning
confidence: 99%
“…After each catalytic cycle, oxTMB and Hg­(II) ions may present on the nanocomposite surface, and thus, the active sites of the nanocomposites are blocked. TMB molecules adsorb on the graphene-based nanocomposites through covalent interactions , and Hg­(II) ions can bind easily with the S-containing sites of TMS/p-rGO-based nanocomposites . Moreover, successive uses and washing of the nanocomposites cause agglomeration of nanoparticles due to the weakening of the van der Waals interactions between the counterparts and thus the catalytic active sites of the nanocomposites become fatigued, which leads to the decrease of catalytic proficiency of the reported nanozyme after each repeated cycle .…”
Section: Resultsmentioning
confidence: 99%